Isolation of quinic acid from dropped Citrus reticulata Blanco fruits: its derivatization, antibacterial potential, docking studies, and ADMET profiling - Heena,; Kaushal, Sonia; Kaur, Vishaldeep; Panwar, Harsh; Sharma, Purshotam; Jangra, Raman (Frontiers in Chemistry, 2024)
Citrus reticulata dropped fruits are generally discarded as waste, causing environmental pollution and losses to farmers. In the present study, column chromatography has been used to isolate quinic acid (1,3,4,5-tetrahydroxycyclohexane-1-carboxylic acid) from the ethyl acetate fraction of a methanol extract of citrus fruits dropped in April. Quinic acid is a ubiquitous plant metabolite found in various plants and microorganisms. It is an important precursor in the biosynthesis of aromatic natural compounds. It was further derivatized into 3,4-o-isopropylidenequinic acid 1,5-lactone (QA1), 1,3,4,5-tetraacetoxycyclohexylaceticanhydride (QA2), and cyclohexane-1,2,3,5-tetraone (QA3). These compounds were further tested for their antibacterial potential against the foodborne pathogens Staphylococcus aureus, Bacillus spp., Yersinia enterocolitica, and Escherichia coli. QA1 exhibited maximum antibacterial potential (minimum inhibitory concentration; 80–120 μg/mL). QA1 revealed synergistic behavior with streptomycin against all the tested bacterial strains having a fractional inhibitory concentration index ranging from 0.29 to 0.37. It also caused a significant increase in cell constituent release in all the tested bacteria compared to the control, along with prominent biofilm reduction. The results obtained were further checked with computational studies that revealed the best docking score of QA1 (−6.30 kcal/mol, −5.8 kcal/mol, and −4.70 kcal/mol) against β-lactamase, DNA gyrase, and transpeptidase, respectively. The absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis revealed that the drug-like properties of QA1 had an ideal toxicity profile, making it a suitable candidate for the development of antimicrobial drugs.